Effect of an antiandrogenic H(2) receptor antagonist on hepatic regeneration in rats - Kahn, D. (1988)
Because biochemical “feminization” of the liver In males is observed with hepatic regeneration and because the hepatic regenerative response in females is greater than that in males, the possibility that antiandrogens might potentiate liver regeneration was investigated. Before 70% hepatectomy, adult male Wistar rats were treated with cimetidine, an antiandrogenic H(2) antagonist, at doses up to 10 times greater than those used clinically. Control animals received either the saline vehicle or ranitidine, an H(2) antagonist without antiandrogenic properties. Treatment with cimetidine reduced the hepatic cytosolic androgen receptor content compared with ranitidine treatment. Hepatectomy caused a further reduction in androgen receptor activity in all groups. Hepatic cytosolic estrogen receptor activity was comparable in all groups throughout the study. Moreover, the rate of liver growth and the levels of ornithine decarboxylase and thymidine kinase activity induced as part of the regenerative response were similar in all groups. Thus, cimetidine, despite its ability to bind to androgen receptors, and ranitidine, an H(2) receptor antagonist without antiandrogen action, do not modulate the hepatic regenerative response to a 70% partial hepatectomy.